Муомала психологияси - Душанов, Р.Х; Хужанова, Д.Р (SCIENCE and SOCIETY, 2025)
This article provides a psychological analysis of the stages of introducing psiological communication for communicating with different types of people: predicting future communication, creating external conditions to facilitate communication, presenting external communicative qualities, clarifying common and neutral areas, eliminating deviations in communication by individual action. Thus, the article reveals the ability to listen to explanations and considerations; the ability to have a psychological impact; the ability to overcome psychological barriers in the process of communication and the possession of positive qualities in communication between law enforcement officers and people of different types, to create a fast reliable psychological connection with them and psychological adaptation to them.
Keywords: psychology of communication; motivational; intelligent; sensual – emotional obstacles; prediction of communication; psychological contagiousness; persuasion; spiritual-sensual determination; self-management; visuality